ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITY OF ETHYL ACETATE FRACTION AND VOLATILE OIL FROM RED GINGER RHIZOME (ZINGIBER OFFICINALE ROSCOE VAR. SUNTI VAL) AS ANTI- ATHEROSCLEROTIC AGENT CANDIDATES - Wakhidatun Suciyati, Siti
Atherosclerosis is an inflammatory disease that last for a long time with unseen progress. In the previous research, the assumption on red ginger as anti atherosclerosis agent is strengthened by lipid profile improvement compared to simvastatin. This study aimed to discover the active fractions from red ginger rhizomes to be developed further as anti-atherosclerosis agents. The selections are based on anti-inflammatory and antioxidant activities. The anti-inflammatory activity is assessed by red blood cell membrane stabilization method. While antioxidant activities are assessed by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) also cupric ion reducing antioxidant capacity (CUPRAC) method. The results showed that 200 µg/ml acetic salicylic acid (77.32 ± 9.97%), 400 µg/ml red ginger rhizomes ethanol extract (42.60 ± 0.87%), 200 and 400 µg/ml ethyl acetate fraction (43.02 ± 8.12% and 52.11 ± 0.30%) also 100, 200 and 400 µg/ml volatile oil (15.72 ± 17.80%; 34.46 ± 11.52%, and 53.99 ± 16.84%) exhibited hemolytic inhibitory activity that statistically significant compared to controls. Antioxidant activity measured by DPPH, ABTS and CUPRAC method revealed red ginger rhizomes ethyl acetate fraction had the lowest IC50 (23.25 ± 10.74 µg/ml; 27.36 ± 6.43 µg/ml; and 15.17 ± 0.60 µg/ml). Blois classification indicated that ethanol extract and ethyl acetate fraction of red ginger rhizomes are potent antioxidants. While red ginger rhizomes essential oils classified as medium antioxidant by DPPH and CUPRAC method, as well as weak antioxidant by ABTS method. In conclusion, ethyl acetate fraction and red ginger rhizomes essential oil are prime candidates for further development as anti-atherosclerotic agents.